2023
DOI: 10.1186/s12913-023-09566-6
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the psychological impact of contact tracing work on staff during the COVID-19 pandemic

Abstract: Background Contact tracing is a key control measure in the response to the COVID-19 pandemic. While quantitative research has been conducted on the psychological impact of the pandemic on other frontline healthcare workers, none has explored the impact on contact tracing staff. Methods A longitudinal study was conducted using two repeated measures with contact tracing staff employed in Ireland during the COVID-19 pandemic using two-tailed independe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
1
1
0
Order By: Relevance
“…Nevertheless, some evidence have showed that while mental health symptoms were elevated among general populations in the early months of the pandemic, there is evidence of a normalisation of rates toward the end of 2020 and early 2021 both globally [ 18 ].This may represent a broad adaptation among the general public to the pandemic, and is in line with the expectation that the majority of people do not develop psychopathologies after natural disasters [ 19 ]. However, Individuals with a history of mental health treatment, loneliness, and lower resilience showed sustained or increased levels of mental health symptoms from March 2020 to April 2021, indicating a heterogenous psychological response to the pandemic that warrants further exploration [ 20 ].…”
Section: Discussionsupporting
confidence: 72%
“…Nevertheless, some evidence have showed that while mental health symptoms were elevated among general populations in the early months of the pandemic, there is evidence of a normalisation of rates toward the end of 2020 and early 2021 both globally [ 18 ].This may represent a broad adaptation among the general public to the pandemic, and is in line with the expectation that the majority of people do not develop psychopathologies after natural disasters [ 19 ]. However, Individuals with a history of mental health treatment, loneliness, and lower resilience showed sustained or increased levels of mental health symptoms from March 2020 to April 2021, indicating a heterogenous psychological response to the pandemic that warrants further exploration [ 20 ].…”
Section: Discussionsupporting
confidence: 72%
“…This is further exemplified by the significant psychological and physiological impact of burnout resulting in higher staff turnover, absenteeism and presenteeism within healthcare organizations ( Kearney et al. , 2020 ) making it difficult to successfully co-design innovate and change within such a challenging context ( Fulham-McQuillan et al. , 2023 ; Byrne et al.…”
Section: Co-design Innovation and Change In Health Systemsmentioning
confidence: 99%